Controlled Release Floating Matrix Tablet of Captopril - N. Abed, Haithem; A. Abdulrasool, Alaa; M. Ghareeb, Mowafaq (Iraqi Journal of Pharmaceutical Sciences, 2017)
The present study was done to prepare a gastroretentive floating tablet of captopril (CAP) which is an angiotensin converting enzyme inhibitor (ACE-inhibitor) used in the treatment of hypertension and heart failure. CAP is mainly absorbed from the proximal intestine and to a lesser extent from the stomach, also CAP stability decreases as the pH raised above 1.2 and this makes it a suitable candidate for floating dosage form.Effervescent floating tablets of CAP were prepared in order to prolong the gastric residence time and increase the bioavailability of the drug. The floating tablets of CAP were prepared by direct compression and wet granulation technique, using the polymer hydroxypropylmethylcellulose (HPMC) as the primary retarding polymer together with carboxymethylcellulose(CMC) ,ethyl cellulose(EC) and pectin as a secondary release modifying polymers in different ratios of (1:1, 3:1 and 9:1). Different formulation parameters were studied such as type of diluents, amount of effervescent agent, methods of preparation and their effects on buoyancy and the in vitro drug release profile as well as their physical characteristics. The wet granulation method shows a good flow and compressibility characteristics and a better dose uniformity in comparison with direct compression technique. Pectin together with HPMC in the ratio of 1:1 was found to meet the requirement for a good matrix formation and floating characteristics and the drug release was sufficiently sustained for 12 h with floating time >24h and floating lag time of 2 min. Kinetic modeling of the release data for the selected formula showed that the mechanism of drug release pattern follows anomalous or non –fickian diffusion. Key words: Captopril, floating, matrix tablet, pectin.